ADAPTIVE LEARNING TECHNOLOGIES IN TEACHING DESCRIPTIVE GEOMETRY IN HIGHER EDUCATION - Yusubjonov Jonibek Farkhod ugli (Modern American Journals, 2025)
Adaptive learning technologies offer personalized educational experiences by dynamically adjusting content, pacing, and feedback based on learner performance and preferences. In higher education, teaching Descriptive Geometry—a discipline requiring spatial reasoning, visualization, and geometric modeling—can benefit significantly from these technologies. This study investigates the implementation of adaptive learning approaches for Descriptive Geometry instruction, focusing on curriculum design, digital tools, and student outcomes. Utilizing the IMRaD framework, the research combines literature review, experimental adaptation of learning platforms, and assessment of student performance and engagement. Results indicate that adaptive learning enhances comprehension, retention, and motivation, while supporting individualized pathways and real-time feedback. The discussion evaluates technological, pedagogical, and methodological considerations, and the conclusion highlights the transformative potential of adaptive learning for Descriptive Geometry education in higher education.
Keywords: Adaptive Learning, Descriptive Geometry, Higher Education, Personalized Education, Digital Learning Platforms, Spatial Reasoning, STEM Education, Student Engagement